2020
DOI: 10.1016/j.arth.2019.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable, Postoperative Risk Factors for Delayed Discharge Following Total Knee Arthroplasty: The Influence of Hypotension and Opioid Use

Abstract: Keywords:total knee arthroplasty opioid hypotension modifiable risk factors length of stay anemia a b s t r a c t Background: We sought to identify independent modifiable risk factors for delayed discharge after total knee arthroplasty (TKA) that have been previously underrepresented in the literature, particularly postoperative opioid use, postoperative laboratory abnormalities, and the frequency of hypotensive events. Methods: Data from 1033 patients undergoing TKA for primary osteoarthritis of the knee betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…Although hypocalcemia frequently occurs after THA (54.93%), clinical symptoms associated with hypocalcemia are extremely rare [57]. Routinely, no intervention would be applied for hypocalcemia, but there is a limited understanding of hypocalcemia in patients after THA, thus warranting additional studies [58].…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Although hypocalcemia frequently occurs after THA (54.93%), clinical symptoms associated with hypocalcemia are extremely rare [57]. Routinely, no intervention would be applied for hypocalcemia, but there is a limited understanding of hypocalcemia in patients after THA, thus warranting additional studies [58].…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…8,9,40,41,44 Concerning total joint arthroplasty, numerous publications have cited preoperative and perioperative opioid use as risk factors for deleterious outcomes after surgery, noting increased health care utilization and increased rates of prosthetic joint infection and revision surgery. 4,6,7,20,56,59 Similar studies have also identified preoperative opioid use as a negative predictor of patient-reported outcome measure scores, with lower preoperative baseline scores and lower overall change in function after arthroplasty. 12,31,32,33,50 A similar relationship has been found in patients undergoing RCR.…”
mentioning
confidence: 72%
“…The MarketScan outpatient services database was queried for data from 2009 to 2018 for patients undergoing arthroscopic RCR using Current Procedural Terminology (CPT) code 29827 (arthroscopy, shoulder, surgical, with RCR). Patients were excluded based on a number of criteria including (1) 6-month noncontinuous preoperative enrollment (ie, patients who were not continuously enrolled in the database for the 6-month period preceding surgery), (2) 3-month noncontinuous postoperative enrollment, (3) no enrollment in the pharmaceutical claims database, (4) open RCR, (5) any concomitant shoulder arthroplasty or humerus/glenoid fracture fixation, (6) those with preoperative cancer diagnoses who may have required opioid medications for chronic cancer pain, and (7) those aged \18 years. Additionally, a second cohort was created with patients who had 3 years of postoperative continuous enrollment and CPT laterality code modifiers for the tracking of longer term revision rates in addition to the criteria above.…”
Section: Data Acquisition and Patient Selectionmentioning
confidence: 99%
“…Other studies such as that of Roshanov et al . [ 56 ] reported hypotensive events in postoperative days 0 and 1 was also found to be associated with increased length of hospital stay (OR 1.305, p = 0.0239) [ 14 , 21 ]; and sepsis/systemic inflammatory response syndrome [ 23 ]. Other outcomes that were investigated were: surgical site infection, that was found to be not statistically significant in relation to MAP <55 mmHg and SBP <80 mmHg, but odds of 1.08 were found in association with minimum postoperative MAP, per 5 mmHg decrease by Yilmaz et al .…”
Section: Resultsmentioning
confidence: 99%